2023
DOI: 10.3389/fnut.2023.1073626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association between dietary salt intake and the risk of atrial fibrillation using Mendelian randomization

Abstract: BackgroundPrevious studies have suggested that dietary salt intake affects atrial fibrillation (AF); however, the causal association between them still remains unclear. Thus, we conducted this Mendelian randomization (MR) study to explore the correlation between them.MethodsGenetic instruments for dietary salt intake were from a genome-wide association study (GWAS), which included 462,630 European individuals. Summary-level data for AF were obtained from another published GWAS (22,068 cases and 116,926 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Our study, along with previous research, found that the association between salt intake and dementia remained significant even after excluding genetic variants associated with hypertension (Faraco et al, 2019;Wang et al, 2023). Conversely, the association between salt intake and VaD was not significant, even when blood pressure-related genetic variants were not excluded (data not shown).…”
Section: Numbersupporting
confidence: 71%
See 1 more Smart Citation
“…Our study, along with previous research, found that the association between salt intake and dementia remained significant even after excluding genetic variants associated with hypertension (Faraco et al, 2019;Wang et al, 2023). Conversely, the association between salt intake and VaD was not significant, even when blood pressure-related genetic variants were not excluded (data not shown).…”
Section: Numbersupporting
confidence: 71%
“…In the context of high salt intake and dementia, MR studies offer a unique opportunity to explore whether there is a causal relationship between these factors. Studies have been conducted using MR methods to assess the health effects of salt added to food and risk factors for dementia (Jin et al, 2022;Sproviero et al, 2021;Wang et al, 2023;Zhou et al, 2021). These studies used inverse-variance weighted (IVW)…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition to the high salt content of the Western diet, followers of this dietary pattern typically add salt to their food and consume more high-salt pickles. 5 This high salt intake is a modifiable risk factor for cardiovascular diseases 6 and may contribute to insulin resistance and metabolic dysfunction via the activation of the renin-angiotensin system. 7 A growing number of individuals are now choosing natural medications, particularly plant-based supplements, for the prevention and treatment of diseases as people's quality of life improves.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition to the high salt content of the Western diet, followers of this dietary pattern typically add salt to their food and consume more high-salt pickles. 5 This high salt intake is a modifiable risk factor for cardiovascular diseases 6 and may contribute to insulin resistance and metabolic dysfunction via the activation of the renin–angiotensin system. 7…”
Section: Introductionmentioning
confidence: 99%